Two new species of Werauhia (Bromeliaceae) with spicate inflorescences from Costa Rica - Cascante-Marín, Alfredo; Trejos-Fernández, Christian; Morales, J. Francisco (Phytotaxa, 2026)
Two new species of epiphytic bromeliads, Werauhia estrellensis and W. picadoi, belonging to the genus Werauhia (Bromeliaceae, Tillandsioideae) are described and illustrated from the mountain forests of Costa Rica. Both species inhabit the Talamanca mountain range at elevations between 1300 and 2200 m a.s.l. Werauhia estrellensis resembles W. barii but it is distinguished by its longer peduncle and green floral bracts, in contrast to yellow brown. Werauhia picadoi is similar to W. vulcanicola but it can be differentiated by its more robust size and acuminate leaf apex, as opposed to the rounded and apiculate apex of W. vulcanicola. Both new species are classified in section Werauhia and they are characterized by their spicate inflorescence, with rugose floral bracts arranged distichously (rather than secund) at anthesis. A key to related species with spicate and rugose floral bracts from southern Central America is included. A preliminary evaluation of their conservation status, based on IUCN criteria, classifies W. estrellensis as Vulnerable (VU D2) and W. picadoi as Least Concern (LC).